Transforming the socio economy with digital innovation. - Watanabe, Chihiro (Elsevier, 2021)
Advances in digital innovations continue to dramatically change daily life, work and the economy. Transforming to a Digital Society and Economy provides deep insights for advancing economic growth in our developing digital world, explaining the underlying techno-economics and our ability to make informed decisions. Using empirical analyses derived from data-driven modeling, Transforming to a Digital Society and Economy explores the impacts of digital innovation on socio-economic phenomena, resilience, and governance. It examines the limitation of using GDP as a measure of economic growth in digital societies, stressing how the Internet promotes a "free" culture that cannot be captured through GDP data. The book synthesizes multi-dimensional research consisting of digital platform ecosystems observations, theoretical appraisals, statistical methods development, in-depth empirical analysis, and database construction for analysis and outcomes compilation. Utilizing analysis from more than 500 global ICT leaders, Transforming to a Digital Society and Economy identifies potential challenges and solutions for academic analysis, economic planning, and policy-making.